A new perceptual convolutive blind source separation algorithm for speech separation - Qiongfeng Pan; Aboulnasr, T. (2004 7th International Conference on Signal Processing : proceedings : ICSP'04 : Aug. 31-Sept 4, 2004, Beijing, China, 2004)
In this paper, we address the problem of blind speech signal separation. A new perceptual convolutive blind source separation algorithm is proposed based on filtered-E LMS algorithm and the masking properties of human auditory system. This algorithm emphasizes frequencies to which the human ear is sensitive and de-emphasizes frequencies that are inaudible to human ear by incorporating the properties of human auditory system making it suitable for speech separation. Simulation results on blind speech signal separation show that the proposed algorithm can improve the separated speech quality and has better convergence performance.